SYNERGISTIC AND EFFLUX PUMP INHIBITORY ACTIVITY OF PLANT EXTRACTS AND ANTIBIOTICS ON STAPHYLOCOCCUS AUREUS STRAINS - Urmila; Jandaik, Savita; Mehta, Jyoti; Mohan, Manindra (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The purpose of this study was to evaluate the synergistic and efflux pump inhibitory activities of some important medicinal plants collected from Western Himalaya against different strains of Staphylococcus aureus to facilitate the reintroduction of therapeutically ineffective antibiotics back into clinical use. Methods: Various plant materials were extracted using methanol, ethyl acetate, and water. The dried extracts were screened for synergistic activity by well diffusion method, and efflux pump inhibitory activity for plants extracts exhibiting maximum synergism assessed by berberine uptake assay and ethidium bromide efflux inhibition assay, respectively. Results: Methanolic extract (ME) and ethyl acetate extracts (EE) of most of the plant extracts showed synergistic activity with ciprofloxacin and norfloxacin, whereas an aqueous extract showed no any synergistic activity. Maximum efflux pump inhibitory activity was observed for ME of Angelica glauca followed by EE of Ficus carica. Conclusion: ME of A. glauca exhibited potentials of efflux pump inhibition, and thus can, be used as an adjuvant with antibiotics to overcome the problem of drug resistance due to efflux. Keywords: Staphylococcus aureus, Therapeutically ineffective antibiotics, Synergistic effect, Efflux pump inhibitors. Â